Penilaian terhadap keberkesanan pengajaran dalam kalangan guru-guru KAFA di Kedah - Awang, Mohd Isha; Daud, Yaakob; Don, Yahya; Kasim, Abd Latif (Universiti Utara Malaysia, 2014)
KAFA education is to produce students who are knowledgeable, high sense of piousness, competent, work righteousness and high morality based on the Quran and Sunnah. Consequently, KAFA was aimed aim to create a conscious and the ability to contribute and improving civilization, race and nation.In order to achieve these goals, it relies heavily on the effectiveness of the teachers' role in the learning process relating to the students. This research was a survey that aimed to gain insight into the effectiveness of teaching practices in the implementation of learning KAFA in Kedah Darul Aman.The study involved 113 teachers and a total of 236 students and questionnaire was used as an instrument to obtain the data.Descriptive analysis was used to describe the teaching practices of the respondents surveyed.The results showed the level of implementation among KAFA teachers in the state of Kedah was high.Teachers also found to have a positive attitude towards teaching.In fact, students have responded positively to the teacher. Several aspects should be given attention such as Kedah Islamic Religious Department should conduct workshops on teaching to help teachers to improve their competencies with updated learning patterns and to face the challenges of current and future needs of students.